Impact of photovoltaic power plants on the overall electric power system of the Republic of Macedonia - Kanevche, Aleksandra; Tomovski, Igor; Kocarev, Ljupco (My University, 2013)
In this paper we analyze the impact of the renewable energy sources on the overall electric power system of the Republic of Macedonia. Specifically, the effect of the photovoltaic power plants is examined. For this purpose we developed an electricity production optimization model, based on standard network flow model. The renewable energy sources are included in the model of Macedonia based on hourly meteorological data. Electricity producers that exist in 2012 are included in the base scenario. Two more characteristic years are analyzed, i.e. 2015 and 2020. The electricity producers planned to be constructed in these two years (which include the renewable energy sources) are also included. The results show that the renewable energy sources introduce imbalance in the system when the minimum electricity production is higher than the electricity required by the consumers. But, in these critical situations the production from photovoltaic energy sources is zero, which means that they produce electricity during the peak load, and do not produce when the consumption is at minimum.
Keywords: power plant, electric power system, electricity consumption and transmission, photovoltaic power plant